Filling the Last Major Gap in the Phylogeny of Lotus (Leguminosae): The Nearly Extinct Lotus benoistii from Morocco, a Potentially Important Breeding Resource - Galina V. Degtjareva; Tahir H. Samigullin; Carmen M. Valiejo-Roman; Cyrille Chatelain; Dmitry D. Sokoloff; Tatiana E. Kramina (Taxonomy)
Lotus, with about 120 species, is the largest genus of Leguminosae–Loteae. The last global classification recognized 14 sections, of which 13 were then sampled in molecular phylogenetic analyses. The section remaining unsampled is Lotus sect. Benedictella with one critically endangered and possibly extinct species, L. benoistii. This is an annual species known from Mediterranean-type vernal pools in the lowlands of northwestern Morocco that differs from other species of the genus in many-seeded indehiscent fruits with thin pericarp and pinnate leaves with 6–9 leaflets. This species was described in a monospecific genus and later transferred to Lotus on the basis of suggested morphological similarities with three mainly desert annuals from North Africa and Southwest Asia currently classified in Lotus sect. Chamaelotus. We provide the first molecular phylogenetic data on L. benoistii and show that it is far from L. sect. Chamaelotus. It is close to plants traditionally classified in Lotus sect. Lotus that have a center of diversity in Europe and temperate Asia. Phylogenetic analyses of plastid markers showed that L. sect. Chamaelotus belongs to a clade with major taxonomic diversity in Macaronesia, Africa, SW Asia, and Australia. Morphology does not provide arguments against the novel hypothesis on the relationships of L. benoistii. Its possible extinction is a great loss for the breeding programs of the pasture plant L. corniculatus. We provide the first anatomical data of L. benoistii, showing that its non-shattering condition has a peculiar nature that differs from all other instances of indehiscence in Loteae.